2007
DOI: 10.1510/icvts.2006.141044
|View full text |Cite
|
Sign up to set email alerts
|

The 'aortic rim' recount: embolization of interatrial septal occluder into the main pulmonary artery bifurcation after atrial septal defect closure

Abstract: Strict selection criteria governing an 'adequate' aortic rim, the size of the device, and the choice of the device may help reduce the incidence of complications like the rare, but potentially fatal embolization of the device into the pulmonary artery following percutaneous device closure of an ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 9 publications
1
38
0
3
Order By: Relevance
“…Furthermore, 2 reports have shown that an anterior margin of less than 5 mm may predispose to early and late device embolization. 29,47 Hypermobility of the interatrial septum was hypothesized to be a risk factor for unsuccessful percutaneous device closure of ASD and PFO. 48 However, an evaluation of 69 device placements at our institution revealed no significant correlation between exaggerated septal mobility and the success of device closure of interatrial communications.…”
Section: Device Embolizationmentioning
confidence: 99%
“…Furthermore, 2 reports have shown that an anterior margin of less than 5 mm may predispose to early and late device embolization. 29,47 Hypermobility of the interatrial septum was hypothesized to be a risk factor for unsuccessful percutaneous device closure of ASD and PFO. 48 However, an evaluation of 69 device placements at our institution revealed no significant correlation between exaggerated septal mobility and the success of device closure of interatrial communications.…”
Section: Device Embolizationmentioning
confidence: 99%
“…1,7,8) Our patient had an aortic rim measuring 2 mm, and margins of < 5 mm may predispose the patient to early and late device embolization. 9) Surgery for retrieval of the device is a proposed treatment, but it carries additional risks including bleeding secondary to antiplatelet therapy. Several transcatheter retrieval techniques of embolized devices have been described using gooseneck snares, pig tail catheters, and bioptomes.…”
Section: Discussionmentioning
confidence: 99%
“…Klinikte öksürük, göğüs kafesinde sıkışma gibi nonspesifik semptomlar görülebilmekle birlikte literatürdeki bir çok olgu sunumunda hastaların asemptomatik oldukları bildirilmiştir (2,3,7) . Embolize olan cihazın potansiyel olarak pulmoner arterde erozyon oluşturarak ölümcül kanamaya yol açma riski bulunmaktadır ve vakit geçirilmeden çıkar-tılması önerilmektedir (8) .…”
Section: Discussionunclassified